(untitled) (The International Journal for Scientific Research, 2024)
This research is used to present the application of Osterwalder & Pigneur (2010) business model on the three e-businesses given in the assignment description. Therefore, the report consists of the business model canvas for all the three companies along with detailed descriptions of each blocks in the canvas and their relevant discussions.